The Influence of Discipline and TPP on Performance Through Achievement Motivation in Civil Servants at The DPRD Secretariat Purwakarta District - Amalia, Dinda; Jumiati, Eti; Ningrum, Intan Rusita (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
This study aims to analyze the effect of discipline and additional employee income (TPP) on performance through achievement motivation as an intervening variable in the State Civil Apparatus at the Purwakarta Regency DPRD secretariat. The data source in this study was obtained from a questionnaire (primary) distributed to respondents. The population of this research is the staff of DPRD Purwakarta. The research sample amounted to 24 people. The research analysis method used is the outer model and inner model test. The research findings show that the direct effect: discipline has no effect on performance (P-Value 0.806 > 0.05); TPP affects performance (P-Value 0.001 < 0.05); achievement motivation affects performance (P-Value 0.00 < 0.05); Discipline affects achievement motivation (P-Value 0.002 < 0.05); TPP has no effect on achievement motivation (P-Value 0.740 > 0.05). Indirect effect: achievement motivation successfully mediates discipline to performance (P-Value 0.003 < 0.05), but achievement motivation does not successfully mediate between TPP to performance (P-Value 0.716 > 0.05).